Dating EU15 monthly business cycle jointly using GDP and IPI - Billio, Monica (OECD Publishing, 2008)
This paper aims at the production of a chronology for the EU15 business cycle by comparing parametric and non-parametric procedures on monthly and quarterly data as well in a combined approach. The main innovation is the joint use of the monthly series for the EU15 Gross Domestic Product (GDP) and the EU15 Industrial Production Index (IPI) from 1970 to 2003. The monthly IPI and the quarterly GDP at the EU15 level have been reconstructed starting from the available national series. The monthly GDP has then been computed using temporal disaggregation techniques. The obtained chronology is directly comparable to ones produced by several authors for the euro area